2021
DOI: 10.3390/su13137066
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Entrepreneurial Intention among Foreigners in Kazakhstan

Abstract: Entrepreneurship is essential in contributing to economic growth, job creation, technological advances, etc. in all countries, including Kazakhstan. Hence, the purpose of this study was to find out how to further facilitate the development of (foreign) entrepreneurship in Kazakhstan. In doing so, the authors attempted to identify factors influencing entrepreneurial intention (EI), specifically among the foreigners in Kazakhstan, and highlight the role of government support (GS) in general and under COVID-19. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 139 publications
0
17
0
1
Order By: Relevance
“…Some research has shown the impact of a combination of contextual factors that may create the right atmosphere for the start of a new project [31]. These factors, such as the availability of financial savings, level of education, government support, and infrastructure form an individual's push or pull towards self-employment [62][63][64].…”
Section: Refugee Context (Rc)mentioning
confidence: 99%
“…Some research has shown the impact of a combination of contextual factors that may create the right atmosphere for the start of a new project [31]. These factors, such as the availability of financial savings, level of education, government support, and infrastructure form an individual's push or pull towards self-employment [62][63][64].…”
Section: Refugee Context (Rc)mentioning
confidence: 99%
“…Extant research has reported mixed results regarding the direct impact of this antecedent on EI [2]. Some confirm it [27,51] while others reported no significant impact [6,14,15,53].…”
Section: Subjective Norms and Entrepreneurial Intentionmentioning
confidence: 98%
“…It has been mentioned that this antecedent of EI comes into play even before a student or an individual starts evaluating business ideas [50]. Further it is elaborated that this factor represents an individual's expectation of positive results, and people with such evaluation of entrepreneurship may create their own venture [51]. An individual's expectations that lead to the personal attitude can also vary.…”
Section: Personal Attitude and Entrepreneurial Intentionmentioning
confidence: 99%
See 2 more Smart Citations